Validation of Physical Performance Tests in Individuals with Advanced Knee Osteoarthritis. Issue 3 (October 2019) - Mehta, Saurabh P.; Morelli, Nathan; Prevatte, Caleb; White, Derrick; Oliashirazi, Ali
Background: Individuals with advanced osteoarthritis (OA) of the knee experience significant impairments in balance and in essential physical functions such as walking and rising from a chair. There is limited evidence on valid outcome measures to capture these impairments. Questions/Purposes: We sought to examine the construct validity of three physical performance measures in patients with advanced knee OA: a gait speed (GS) test, the Short Physical Performance Battery (SPPB), and the Timed Up and Go (TUG) test. Methods: We designed a cross-sectional clinical measurement study in which patients with advanced knee OA completed two self-reported measures: the Knee Injury and Osteoarthritis Outcome Score—Physical Function Shortform (KOOS-PS) and a four-part numeric pain rating scale (Q-NPRS). They were also administered the GS test, TUG test, and SPPB. Convergent and divergent construct validity were assessed by examining relationships between the GS test, the SPPB, the TUG test, the KOOS-PS, and the Q-NPRS and calculating Pearson correlation coefficients ( r ). The scores for the GS, TUG test, and SPPB were compared with established normative values for age-matched healthy controls. Results: Forty-four subjects (mean age, 66.9 ± 8.1 years) participated in the study. The GS test showed low concordance with the SPPB component tests and the TUG test. The relationships between the physical performance measures and the self-reported measures were low. The scores for the GS test, TUG test, and SPPB in our sample were significantly worse when compared with age-matched normative values, indicating impairments in physical performance. Conclusion: These results advance the understanding of the validity of the GS test, TUG test, and SPPB in demonstrating the impairments in physical performance that patients with advanced knee OA experience in walking, balancing, and rising from a chair. Future research should examine the reproducibility and responsiveness of the GS test, TUG test, and SPPB in patients with advanced knee OA, in order to facilitate the integration of these measures into clinical practice.